THE LOSS OF POTASSIUM FROM FROG NERVES IN ANOXIA AND OTHER CONDITIONS - Fenn, Wallace O. (The Rockefeller University Press, 1950)
1. Frog nerves immersed in Ringer's solution lose on the average 23 per cent more potassium if the solution is equilibrated with pure nitrogen than if equilibrated with oxygen. 2. Tying off the ends of the nerves during immersion increased rather than diminished the loss of potassium. 3. There was some evidence that nerves tended to regain potassium if they were returned to oxygen after a period of anoxia. 4. Addition of acetylcholine to the solution increases the loss of potassium. 5. Equilibration of the solution and nerves with 20 per cent CO(2) in O(2) increases the loss of K from nerves in Ringer's solution but decreases it in frog blood.